Delays in HIV-1 infant polymerase chain reaction testing may leave children without confirmed diagnoses in the Western Cape province, South Africa - Kamela L. Mahlakwane; Wolfgang Preiser; Nokwazi Nkosi; Nasheen Naidoo; Gert van Zyl (AOSIS, 2022)
Background: Early diagnosis and confirmation of HIV infection in newborns is crucial for expedited initiation of antiretroviral therapy. Confirmatory testing must be done for all children with a reactive HIV PCR result. There is no comprehensive data on confirmatory testing and HIV PCR test request rejections at National Health Laboratory Service laboratories in South Africa. Objective: This study assessed the metrics of routine infant HIV PCR testing at the Tygerberg Hospital Virology Laboratory, Cape Town, Western Cape, South Africa, including the proportion of rejected test requests, turn-around time (TAT), and rate of confirmatory testing. Methods: We retrospectively reviewed laboratory-based data on all HIV PCR tests performed on children ≤ 24 months old (n = 43 346) and data on rejected HIV PCR requests (n = 1479) at the Tygerberg virology laboratory over two years (2017-2019). Data from sample collection to release of results were analysed to assess the TAT and follow-up patterns. Results: The proportion of rejected HIV PCR requests was 3.3%; 83.9% of these were rejected for various pre-analytical reasons. Most of the test results (89.2%) met the required 96-h TAT. Of the reactive initial test results, 53.5% had a follow-up sample tested, of which 93.1% were positive. Of the initial indeterminate results, 74.7% were negative on follow-up testing. Conclusion: A high proportion of HIV PCR requests were rejected for pre-analytical reasons. The high number of initial reactive tests without evidence of follow-up suggests that a shorter TAT is required to allow confirmatory testing before children are discharged.